Realizing ultrafast oxygen evolution by introducing proton acceptor into perovskites - She, Sixuan (2021)
The oxygen evolution reaction (OER) is of prime importance in multiple energy storage devices. Perovskite oxides involving lattice-oxygen oxidation are generally regarded as highly active OER catalysts, but the deprotonation of surface-bound intermediates limit the further activity improvement. Here, it is shown that this kinetic limitation can be removed by introducing Sr₃B₂O₆ (SB) which activates a proton-acceptor functionality to boost OER activity. As a proof-of-concept example, an experimental validation is conducted on the extraordinary OER performance of a Sr(Co₀.₈Fe₀.₂)₀.₇B₀.₃O₃₋δ (SCFB-0.3) hybrid catalyst, made using Sr₀.₈Co₀.₈Fe₀.₂O₃₋δ as active component and SB as a proton acceptor. This smart hybrid exhibits an exceptionally ultrahigh OER activity with an extremely low overpotential of 340 mV in 0.1 M KOH and 240 mV in 1 M KOH required for 10 mA cm⁻² which is the top-level catalytic activity among metal oxides reported so far, while maintaining excellent durability. The correlation of pH and activity study reveals that this enhanced activity mainly originates from the improved interfacial proton transfer. Such a strategy further demonstrated to be universal, which can be applied to enhance the OER activity of other high covalent oxides with close O 2p-band centers relative to Fermi energy.